LEGAL ANALYSIS OF VIOLATION OF PRIVACY RIGHTS BY SHOPEE EXPRESS COURIERS WHEN PHOTOGRAPHING CONSUMERS AS PROOF OF RECEIPT OF GOOD - Wulandari , Shofia Eka Putri; Multazam, Mochammad Tanzil (Antis Publisher, 2024)
General Background: The rapid growth of e-commerce in Indonesia has brought to light critical issues regarding privacy rights, particularly in the context of delivery services. Specific Background: This research specifically addresses the actions of Shopee Express couriers who take photos of package recipients without their consent, raising significant concerns regarding personal data protection and privacy violations. Knowledge Gap: Despite the existence of laws aimed at protecting personal data, there is insufficient analysis of how these laws apply to courier practices in e-commerce. Aims: The study aims to examine the legal implications of these privacy violations and the adequacy of existing regulations in safeguarding consumer rights. Results: Utilizing a normative juridical methodology with a statutory approach, the findings indicate that such actions contravene multiple Indonesian laws, including the 1945 Constitution, Law No. 8 of 1999, and various governmental regulations concerning data protection. Novelty: This research adds to the existing literature by highlighting the intersection of e-commerce practices and privacy law, emphasizing the need for more robust legal frameworks. Implications: The findings suggest that enhanced policies and stricter law enforcement are necessary to protect consumer privacy rights effectively and maintain public trust in Shopee Express services. Potential sanctions for couriers include warnings and civil lawsuits, reinforcing the importance of accountability in the delivery sector.